Depth Maps Fast Scalable Compression Based On Coding Unit Depth - Mosbah, Sonia; Sebai, Dorsaf; Ghorbel, Faouzi (Proceedings - International Conference on Image Processing, 2020)
SHVC, the Scalable extension of the High Efficiency Video Coding standard (HEVC), combines large compression efficiency and high visual quality of different versions of a same video in a single bitstream. However, this comes at the cost of a high computational complexity. Many efforts aim to reduce this latter for texture images. In this paper, we aim at the same objective, but for depth maps that are characterized by areas of smoothly varying grey levels separated by sharp discontinuities at object boundaries. Typically, we propose a fast scalable coding scheme while exploiting depth maps specificities, depth information of SHVC Coding Units (CUs) as well as correlation between base and enhancement layers. Experimental results show that the proposed method significantly reduces the execution time of the SHVC encoder; while maintaining the quality of intermediate views synthesized from encoded depth maps.